Hubungan Tingkat Pengetahuan Dan Motivasi Perawat Dengan Kepatuhan Five Moments Hand Hygiene Di Ruang Rawat Inap Rumah Sakit Umum Muhammadiyah Siti Aminah Bumiayu Tahun 2023 - Ahmad Zakiudin; Diah Nur Aisyah (STIKes Ibnu Sina Ajibarang, 2024)
Five moments hand hygiene is a program carried out by WHO to overcome HAIs. The implementation of this program is influenced by various things such as the knowledge and motivation of nurses. The aim of the research was to determine whether there was a relationship between the level of knowledge and motivation of nurses and compliance with five moments hand hygiene in the inpatient room at RSU Muhammadiyah Siti Aminah Bumiayu.The design of this research is descriptive correlative with a cross sectional approach. The research variables are knowledge, motivation and compliance with five moments hand hygiene. The research sample was taken as a total sampling of 50 nurses at RSU Muhamamdiyah Siti Aminah Bumiayu. Data collection was carried out using questionnaires and observation sheets. Data were analyzed using Chi Square with significance α≥0.05.The results showed that the majority of nurses with a good level of knowledge were 32 people (72%) who complied, 23 (46%) did not comply with the implementation of five moments hand hygiene, 9 (10%) and all nurses with moderate motivation, 43 (64%) complied. towards five moments hand hygiene 32 (64%) and non- compliance 11 (22%). The results show that there is no relationship between the level of nurses' knowledge and five moments hand hygiene compliance (ρ=0.345) and there is a relationship between nurses' motivation and five moments hand hygiene compliance (ρ=0.345) at RSU Muhammadiyah Siti Aminah Bumiayu. Motivation is needed by nurses to comply with the five moments of hand hygiene. Supervision and training are expected to increase nurses' motivation to be able to prevent and control infections in hospitals.